A Multicenter Study Evaluating the Stages of Change in Food Consumption with Warning Labels among Chilean University Students - Duran Aguero, Samuel; Araneda, Jacqueline; Ahumada, Danay; Silva Rojas, Jaime; Buhring Bonacich, Rodrigo; Caichac, Astrid; Fernandez Salamanca, Marcelo; Villarroel, Pia; Fernandez, Eloina; Pacheco, Viviana; Aravena Martinovic, Paola Andrea; Wilson, Waleska; et al. (My University, 2020)
Objective. To analyze the stage of change in food consumption with warning labels among Chilean university students. Materials and Methods. Cross-sectional study which applied surveys in universities from all over the country. Study included 4807 participants of 18 to 40 years of both sexes who were asked about the level of knowledge of the new food law and food consumption with warning signals, including questions regarding their willingness to behavior change according to Prochaska's transtheoretical model. To compare continuous variables, Student's t-test was used in the statistical package SPSS 22.0, and p Results. Of the total number of respondents, 99.3% of the students indicated that they know about the food law, classifying foods with signals in the precontemplation stage. Compared by sex, we observed that women give greater importance to behavior change in all of foods (p <0.001). Underweight students give less importance to change in unhealthy foods, while obesity students give more importance but do not show more confidence in behavior change (p <0.05). Conclusion. The university students show a low importance and confidence to make behavior change, aspects associated with sex and nutritional status. It is necessary to strengthen nutritional food education and not just talk about structural measures.
Keywords: Transtheoretical model; Underweight; Consumption